2017
DOI: 10.1002/bit.26310
|View full text |Cite
|
Sign up to set email alerts
|

Nano hydroxyapatite‐blasted titanium surface affects pre‐osteoblast morphology by modulating critical intracellular pathways

Abstract: Although, intracellular signaling pathways are proposed to predict the quality of cell-surface relationship, this study addressed pre-osteoblast behavior in response to nano hydroxyapatite (HA)-blasted titanium (Ti) surface by exploring critical intracellular pathways and pre-osteoblast morphological change. Physicochemical properties were evaluated by atomic force microscopy (AFM) and wettability considering water contact angle of three differently texturized Ti surfaces: Machined (Mac), Dual acid-etching (DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 28 publications
5
52
0
4
Order By: Relevance
“…As reported previously elsewhere [17], there are considerable differences in the topography of the titanium-based surfaces evaluated in this study, mainly documented by atomic force microscopy (insert in Fig. 1).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…As reported previously elsewhere [17], there are considerable differences in the topography of the titanium-based surfaces evaluated in this study, mainly documented by atomic force microscopy (insert in Fig. 1).…”
Section: Resultssupporting
confidence: 68%
“…Three different titanium surfaces (discs) were investigated in this study, distinguishing by the surface properties, called Machined (Mc; control), Dual Acid-Etched (DAE), and acid-etched nanoHA-blasted (nHA). The nHA was obtained by using the Promimic HAnano-method, a detailed description can be found elsewhere [15][16][17]. Briefly, the samples were dipped into a stable particle suspension containing 10 nm in diameter HA particles followed by a heat treatment at 550 • C for 5 min in nitrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Cell Adhesion Was Assayed by Violet Crystal : For the adhesion approach, MC3T3‐E1 cells were treated properly with the both LDH samples up to 24 h. Then, the cells were trypsinized, resuspended in conventional medium containing LDH, counted in hematological chamber, and plated (25 000 cells cm −2 ) in 96‐well plates . After plating, cell adhesion was estimated by incorporation of crystal violet dye at the 3 h and 24 h postplating times.…”
Section: Methodsmentioning
confidence: 99%
“…Among the biomaterials, those devoted to bioengineering protocols need to recapitulate the wound‐healing steps triggering a moderate inflammatory cascade activating hemostasis and later requiring platelets and fibrinogen. In this context, advances in physics and chemistry area allowed the application of nanoscaled structures on modifying and functionalizing molecules/materials, ameliorating their performance in medical proposes . It is not new the purpose of layered double hydroxides (LDHs) as biomaterial .…”
Section: Introductionmentioning
confidence: 99%
“…Regrettably, serious preclinical concerns remain, the signaling cross talk with cells and biomaterials proposes are still the challenge for this promising therapeutic modality . Thus, we have explored and suggested in vitro approaches to predict the quality of the cell/biomaterial interaction, suggesting the intracellular signaling as a preliminary and reliable tool on this matter . Overall, we have shown that cells actively respond to biomaterials modifying their morphology as an immediate consequence of a well‐orchestrated cytoskeleton rearrangement upon integrin activation, where the phosphorylation of cofilin drives actin filaments rearrangement and governs cell adaptation on the substrate.…”
Section: Introductionmentioning
confidence: 99%